2020
DOI: 10.1038/s41586-020-2250-8
|View full text |Cite
|
Sign up to set email alerts
|

A lower X-gate in TASK channels traps inhibitors within the vestibule

Abstract: TASK channels are unusual members of the two-pore domain potassium (K2P) channel family, found in neurons 1 , cardiomyocytes 2-4 and vascular smooth muscle cells 5 where they are involved in regulation of heart rate 6 , pulmonary artery tone 5,7 , sleep/wake cycles 8 and responses to volatile anaesthetics 8-11. K2P channels regulate the resting membrane potential, providing background K + currents controlled by numerous physiological stimuli 12-15. Unlike other K2P channels, TASK channels have the capacity to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
106
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(112 citation statements)
references
References 51 publications
5
106
1
Order By: Relevance
“…TASK-1 binds its inhibitors highly selective, with strong affinity and extremely low washout rates. Recently, Rödström et al (2020) have been able to solve the structure of human TASK-1 by X-ray crystallography. They could show that high-affinity inhibitors are trapped in a vestibule below the selectivity filter by an X-gate, leading to the above mentioned low washout rates (Rödström et al, 2020).…”
Section: Inhibitors Of Task-1mentioning
confidence: 99%
See 1 more Smart Citation
“…TASK-1 binds its inhibitors highly selective, with strong affinity and extremely low washout rates. Recently, Rödström et al (2020) have been able to solve the structure of human TASK-1 by X-ray crystallography. They could show that high-affinity inhibitors are trapped in a vestibule below the selectivity filter by an X-gate, leading to the above mentioned low washout rates (Rödström et al, 2020).…”
Section: Inhibitors Of Task-1mentioning
confidence: 99%
“…Recently, Rödström et al (2020) have been able to solve the structure of human TASK-1 by X-ray crystallography. They could show that high-affinity inhibitors are trapped in a vestibule below the selectivity filter by an X-gate, leading to the above mentioned low washout rates (Rödström et al, 2020). The entrapment has to be considered when interpreting data from pharmacokinetic-pharmacodynamic studies as inhibitors will remain bound and active for a longer time than predicted by these studies.…”
Section: Inhibitors Of Task-1mentioning
confidence: 99%
“…It has recently been shown that some K2P channels possess a lower gate analogous to the classical helix bundle crossing found in many other types of K + channels (Li et al, 2020;Rodstrom et al, 2020). However, most K2P channels, including TREK channels, do not have a lower gate (Brohawn et al, 2012;Miller and Long, 2012;Lolicato et al, 2014;Dong et al, 2015;Lolicato et al, 2017).…”
Section: Introductionmentioning
confidence: 98%
“…It has recently been shown that some K2P channels possess a lower gate analogous to the classical helix bundle-crossing found in many other types of K + channels (Li et al, 2020;Rödstrom et al, 2020). However, most K2P channels, including TREK channels, do not have a lower gate (Brohawn et al, 2012;Miller and Long, 2012;Lolicato et al, 2014;Dong et al, 2015).…”
Section: Introductionmentioning
confidence: 98%